Legal Problems of qualification of euthanasia in Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article deals with the problem of the legal qualification of euthanasia in Kazakhstan, as well as proposals to allocate an independent structure less dangerous kind of murder. Key words: euthanasia, murder, criminal liability, criminal skills, the right to life, the right to die.